Investigation on the mechanical properties of topologically optimized cellular structures for sandwiched morphing skins. (15th October 2020) - Chang, Lulu; Shen, Xing; Dai, Yuke; Wang, Taoxi; Zhang, Lei
Abstract: The mechanical performances of sandwiched morphing skin used for morphing aircraft are principally determined by the cellular substructure undertaking morphing stress. In this paper, in order to guide the design of sandwiched morphing skins utilized in different morphing applications, several optimal topologies of cellular-based structures are calculated, and the mechanical properties of them are evaluated. Initially, the topology optimization technique is utilized to minimize stiffness in the direction of deformation. This is followed by establishing 3D models through post-processing. Then the experiments and finite element analyses are performed to evaluate the designs and compare them with conventional regular honeycomb structure as well as zero Poisson's ratio structure. Among them, a novel load transmitting block is designed for transferring shear load using axial movement. The simulated and experimental results show the superiority of optimized topologies. Also, the consistency of them guarantees the reliability of finite element model. Based on it, this research investigates the mechanical performances of periodic cellular structures and the influence depending on the number of cells. The results of the effective transverse modulus, the effective shear modulus, the out-of-plane displacement and the twist angle give support for the development of sandwiched morphing skins in real applications.